Problems In Cleft Lip Nose Patients Undergoing Augmentation Rhinoplasty With Rib Graft : A Case Report - Kusumastuti, Nadia; Sudjatmiko, Gentur (Jurnal Plastik Rekonstruksi, 2012)
Correction of a cleft lip nasal deformity remains a challenging procedure in reconstructive surgery. Many different procedures have been suggested to address the problem, but few techniques have worked well and consistently. We present a case of secondary cleft nasal deformity after repair of unilateral complete cleft lip and palate on the left side. The corrective procedures carried out included closed method rhinoplasty and dorsal nasal augmentation with rib graft which was fixed to the nasal septum with needle. The patient showed satisfactory immediate post-operative result, with correction of depressed alar base and satisfying dorsal and tip projection. However, 5 months post operative result showed deviation of nasal tip to the cleft side, which we suspected was due to: warping of the rib graft, soft tissue deficiency in the cleft side which exerts pulling forces to the warping graft, and lack of rigid fixation of the graft. After appraising pitfalls encountered in augmenting nasal dorsum of cleft patients with rib graft, we concluded that some preventive measures need to be done to avoid those problems, namely: balanced cross sectional carving of rib graft, cantilever graft with plate and screw to the nasal bone, and addressing pulling force from lack of soft tissue in the cleft side by adding columellar strut graft or alar contour graft.